Distinct Mid-Latitude Eurasian Rossby Wave Trains Preceding Strong and Weak Cold Surges in Southern China - Lin, Juanjuan; Cheung, Ho-Nam (Frontiers in Earth Science, 2022)
This study investigates the large-scale circulation anomalies of strong and weak cold surges in southern China. Results show that the strong and weak surges are associated with a distinct Rossby wave train across Eurasia projecting onto the Scandinavia (SCAND) and Eurasian (EU) patterns. On one hand, the strong surge is preceded by a positive SCAND pattern and a transition of the EU pattern from its negative to positive phase. The corresponding wave train propagates southeastward from East Asia to the North Pacific. This is associated with a strong intensification of the Siberian high, a deepened East Asian trough, and a sharp meridional pressure gradient between northern and southern China; these advect intense cold air masses from Siberia to southern China. On the other hand, the weak surge is preceded by a negative SCAND pattern and a positive EU pattern. The corresponding wave train does not propagate from East Asia to the North Pacific. This wave train has a weak impact on the East Asian winter monsoon circulation and corresponds to weak cold air advections towards southern China. Overall, the intra-seasonal variation of the Eurasian teleconnection patterns is crucial for a comprehensive understanding of the cold surge in southern China.